Smoke and mirrors? Conflict of interest declarations in tobacco and e-cigarette-related academic publications - McDonald, A.; McCausland, K.; Thomas, L.; Daube, Mike; Jancey, Jonine (2023)
Objective: This research explored international tobacco control experts’ level of satisfaction with conflict of interest (COI) declaration processes; and the transparency of COI declarations of identified authors publishing in the tobacco, e-cigarette, and related novel products academic literature. Methods: This case study profiled 10 authors’ (identified by expert panel) COIs pertaining to the tobacco industry; identified the 10 authors’ publications (2010-2021); and assessed the transparency of the COI declarations within the publications. Results: All authors received indirect or direct funding from the tobacco industry. On review of the authors’ 553 publications, 61% of COI and funding declarations were accessible, 33% were partially accessible and 6% were inaccessible. Overall, 33% of authors provided complete COI declarations, 51% provided incomplete declarations, and 16% provided no declaration. Conclusion: This research demonstrates existing guidelines and recommendations for reporting COI declarations are not sufficiently robust to ensure transparency in reporting of COI declarations within the field. Implications for public health: Research outcomes have the potential to define public health discourse and influence public opinion, practices, and policy. It is critical that research remains independent and protected from the influence of the tobacco industry. Processes for monitoring and enforcing accurate reporting of COI declarations are needed.